Low vitamin D concentrations and BMI are causal factors for primary biliary cholangitis: A mendelian randomization study - Xu, Honglin; Wu, Ziyan; Feng, Futai; Li, Yongzhe; Zhang, Shulan (Frontiers in Immunology, 2022)
Backgrounds: Observational studies have identified associations between smoking, alcohol use, body mass index (BMI), and the levels of vitamin D with primary biliary cholangitis (PBC). However, there was lack of randomization control studies to estimate the casual relationship. This study was to investigate the causal estimates for the effects of those risk factors on PBC. Methods: The genetic instrument variants were extracted from genome-wide association studies in European ancestry. Two-sample mendelian randomization (MR) and multivariable mendelian randomization were used to determine genetically causal estimates. Primary analyses consisted of random-effects and fix-mode inverse-variance-weighted methods, followed by secondary sensitivity analyses to verify the results. Results: Our study showed that BMI was a causal factor for PBC (OR 1.35; 95% CI=1.03-1.77; p=0.029). In addition, we found that serum vitamin D levels had a protective effect on PBC after adjusting for BMI (OR 0.51; 95% CI=0.32-0.84; p=0.007). However, we failed to identify evidence supporting that genetic causal effect of smoking and alcohol intake were associated with PBC in European countries. Conclusion: Our results enriched findings from previous epidemiology studies and provided evidence from MR that serum vitamin D concentrations and BMI were independent causal factors for PBC, suggesting that ensuing vitamin D sufficiency and healthy lifestyles might be a cost-effective measure for early intervention for PBC.